Development Strategic Farming System of Local Coffee in Kepulauan Yapen Regency-Province of Papua - Elias Edison Kapitarau; Slamet Hartono; Irham Irham (Agro Ekonomi, 2016)
This research conducted in KepulauanYapen Regency Province of Papua. Objectives of this research to: (1) knowing and explaining internal factors (weakness and strength) and factors of external (threat and opportunity) farming system of local coffee KepulauanYapen Regency Province of Papua, (2) Formulating for development strategy of farming system local coffee correct to be applied in KepulauanYapen Regency Province of Papua. Method used in this study is descriptive analysis method. Determine of location done by purposive. Data part of primary and secondary data. Samples of respondent counted 40 and for Analysis of data using SWOT method. Result of SWOT analysis and IFAS-EFAS matrix show development of farming system district Kepulauan Yapen Province of Papua reside in II quadrant with weakness factor and opportunity more uppermost than threat and strength. Weakness more uppermost at that is exploiting of land in farming system of local coffee, plantation local coffee which have is old, not plant superioring seed of local of coffee, widespread land of farming location and the limited officer of extension agent (PPL). While opportunities which must be exploited wide of farming area, land is fertile and climate supporting growth coffee crop.Using superioring seed will be able to increase product and productivity local coffee. Formulation of the core strategies that should be used as a local coffee farm development strategy in KepulauanYapenRegency namely; optimizing land, improving farming techniques,  to establish areas of local development of coffee farming an affordable, performing a selection  of local coffee varieties and build the garden collection, increase farmers’ land ownership status are certified, Pursue partnerships and improve human resources/ farmers local coffee in KepulauanYapen Regency.